Perbelanjaan Perkahwinan Bagi Masyarakat Muslim: Analisis Literatur - Syed Husin, Syh Noorul Madihah; Hj Azahari, Raihanah; Ab. Rahman, Asmak (Jurnal Fiqh, 2016)
Marriage expenses is a necessity within the process of a marriage. In Muslim community, the couple will start spending for a wedding preparations before actual marriage. Couples who plan to marry must provide a certain amount of money to ensure that their desire to marry is realized. There are various studies which link to marriage expenses for the Muslim community. This article will review on marriage expenses for Muslim community in various forms of writing such as academic books, dissertations, theses and journal articles. This study found that there are four themes discussed in the topic. Generally, studies in these themes only discuss issues related to the marriage expenses indirectly without providing any review on how Muslim community manages it. This study found that there is a need to conduct a special study on this topic to fill the gap in regards of Muslim family studies. This is to provide a comprehensive review and analysis of the Muslim community expenses from the perspective of marriage legislation.